NDUFA4L2 reduces mitochondrial respiration resulting in defective lysosomal trafficking in clear cell renal cell carcinoma. Issue 1 (31st December 2023) - Kubala, Jaclyn M.; Laursen, Kristian B.; Schreiner, Ryan; Williams, Ryan M.; van der Mijn, Johannes C.; Crowley, Michael J.; Mongan, Nigel P.; Nanus, David M.; Heller, Daniel A.; Gudas, Lorraine J.
ABSTRACT: In clear cell renal cell carcinoma (ccRCC), activation of hypoxic signaling induces NADH dehydrogenase (ubiquinone) 1 alpha subcomplex, 4-like 2 (NDUFA4L2) expression. Over 90% of ccRCCs exhibit overexpression of NDUFA4L2, which we previously showed contributes to ccRCC proliferation and survival. The function of NDUFA4L2 in ccRCC has not been fully elucidated. NDUFA4L2 was reported to reduce mitochondrial respiration via mitochondrial complex I inhibition. We found that NDUFA4L2 expression in human ccRCC cells increases the extracellular acidification rate, indicative of elevated glycolysis. Conversely, NDUFA4L2 expression in non-cancerous kidney epithelial cells decreases oxygen consumption rate while increasing extracellular acidification rate, suggesting that a Warburg-like effect is induced by NDUFA4L2 alone. We performed mass-spectrometry (MS)-based proteomics of NDUFA4L2 associated complexes. Comparing RCC4-P (parental) ccRCC cells with RCC4 in which NDUFA4L2 is knocked out by CRISPR-Cas9 (RCC4-KO-643), we identified 3, 215 proteins enriched in the NDUFA4L2 immunoprecipitates. Among the top-ranking pathways were "Metabolic Reprogramming in Cancer" and "Glycolysis Activation in Cancer (Warburg Effect)." We also show that NDUFA4L2 enhances mitochondrial fragmentation, interacts with lysosomes, and increases mitochondrial-lysosomal associations, as assessed by high-resolution fluorescence microscopy and live cell imaging. We identified 161 lysosomal proteins, including Niemann-Pick Disease Type C Intracellular Cholesterol Transporters 1 and 2 (NPC1, NPC2), that are associated with NDUFA4L2 in RCC4-P cells. RCC4-P cells have larger and decreased numbers of lysosomes relative to RCC4 NDUFA4L2 knockout cells. These findings suggest that NDUFA4L2 regulates mitochondrial-lysosomal associations and potentially lysosomal size and abundance. Consequently, NDUFA4L2 may regulate not only mitochondrial, but also lysosomal functions in ccRCC.